1985
DOI: 10.1159/000180104
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Intolerance in Gonadal Dysgenesis: Evidence for Insulin Resistance and Hyperglucagonemia

Abstract: To determine the pathogenesis of carbohydrate intolerance associated with gonadal dysgenesis, plasma glucose, insulin, glucagon, and growth hormone responses to oral glucose and intravenous tolbutamide, arginine and insulin were evaluated in 21 nonobese patients, 7–19 years old. Glucose intolerance was present in 9 of 21 nonobese patients (42.8%). Insulin levels, the area under the insulin curve after oral glucose and intravenous tolbutamide and the insulin to glucose ratio were significantly greater in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…impaired carbohydrate tolerance is frequently observed, the incidence has previously been reported as 26-43% [29][30][31]. This is due to a combination of inadequate insulin release and resistance to insulin at least in part due to disturbed intestinal glucoregulation [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…impaired carbohydrate tolerance is frequently observed, the incidence has previously been reported as 26-43% [29][30][31]. This is due to a combination of inadequate insulin release and resistance to insulin at least in part due to disturbed intestinal glucoregulation [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, hyperinsulinism is present followed by a decrease in (Tcell reserve, and. finally, beyond the third decade of life, overt diabetes mellitus occurs in 15% of women with TS [31,32,34], Both GH and anabolic steroids affect carbohydrate metabolism. GH has been shown to antagonize insulin actions and in normal people may lead to increased blood glucose and insulin levels associated with impaired glu cose utilization [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests defective suppression of the Randle cycle, perhaps mediated in part by the inappropriately low level of insulin [20]. Several studies have found a positive family history of type 2 diabetes, with an unusually high frequency, but this does not seem to explain the observed glucose intolerance, since Turner’s patients with a negative family history also exhibit these characteristics [19, 21, 22, 23]. Intervention studies in postmenopausal women have shown that transdermal 17β-oestradiol exerts either moderately positive effects on glucose metabolism [24]or no effect at all [25].…”
Section: Glucose Metabolism Body Composition and Physical Fitnessmentioning
confidence: 99%
“…Girls with TS have an even higher incidence of impaired glucose tolerance [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12]and, therefore, an increased risk of developing diabetes mellitus in adulthood [2, 3, 5, 6, 13]. Stoppoloni et al [14]showed an increase in insulin resistance in 4 patients with TS (age 13–21 years) using an euglycaemic hyperinsulinaemic glucose clamp technique.…”
Section: Introductionmentioning
confidence: 99%